The United Nations and terrorism: Germany, multilateralism, and antiterrorism efforts in the 1970s - Blumenau, Bernhard (Palgrave Macmillan, 2014)
Domestic terrorism in Germany in the 1970s -- Case studies in international terrorism : hostage crises and hijackings -- The Ad Hoc Committee on International Terrorism, the diplomats convention, and the UN Hostages Convention : drafting and launch -- The UN Hostages Convention : negotiations and adoption -- Conclusions : Germany and UN antiterrorism efforts in the 1970s and beyond